WHICH HYPOTHESIS IS VALID FOR OECD COUNTRIES IN THE CONTEXT OF THE RELATIONSHIP BETWEEN ENERGY CONSUMPTION AND ECONOMIC GROWTH?A PANEL DATAANALYSIS - Sugozu, Ibrahim Halil; Yasar, Sema (Russian Acad Sciences, Ural Branch, Inst Economics, 2023)
In the study, panel data analysis was conducted on 32 OECD countries covering the period 1990-2018. To analyse the effect of energy consumption on economic growth, first, a cross-section de-pendence test of the variables was carried out, then CADF Test, which is the most suitable unit root test based on the obtained results results, was applied. According to the findings of the Hausman, autocor-relation, and heteroscedasticity tests, it has been decided to use the Driscoll-Kraay test for the model's forecast. The forecast results demonstrate that energy consumption positively affects economic growth. Westerlund ECM Panel Cointegration Test was conducted to determine the long-term relationship, and it concluded that the variables acted together in the long term. Emirmahmutoglu & Kose and Dumitrescu & Hurlin tests were used to determine the direction of the relationship between energy consumption and growth. Through the results of both tests, a maximum number of countries emerged respectively in the null hypothesis with no causality relationship and then in the growth hypothesis explaining the causality relationship from energy to growth. Along with the panel fisher and panel Z_NT test results of both cau-sality tests, a causality relationship has been detected from energy to growth.
Keywords: OECD countries; energy; energy consumption; energy policies; energy and growth relationship hypotheses; economic growth; economic policies; panel data analysis; panel causality test; CADF test